Preliminary analysis of double‐negative T, double‐positive T, and natural killer T‐like cells in B‐cell chronic lymphocytic leukemia - Luciana Valvano; Filomena Nozza; Giovanni D'Arena; Fiorella D'Auria; Luciana De Luca; Giuseppe Pietrantuono; Giovanna Mansueto; Oreste Villani; Simona D'Agostino; Daniela Lamorte; Giovanni Calice; Teodora Statuto (Cancer Medicine, 2023)
Abstract Background B‐cell chronic lymphocytic leukemia (B‐CLL) is characterized by the expansion of CD5+ malignant B lymphocytes. Recent discoveries have shown that double‐negative T (DNT) cells, double‐positive T (DPT) cells, and natural killer T (NKT)‐cells may be involved in tumor surveillance. Methods A detailed immunophenotypic analysis of the peripheral blood T‐cell compartment of 50 patients with B‐CLL (classified in three prognostic groups) and 38 healthy donors (as controls) matched for age was performed. The samples were analyzed by flow cytometry using a stain‐lyse‐no wash technique and a comprehensive six‐color antibody panels. Results Our data confirmed a reduction in percentage values and an increase in absolute values of T lymphocytes in patients with B‐CLL, as already reported. In particular, DNT, DPT, and NKT‐like percentages were significantly lower than in the controls, except for NKT‐like in the low‐risk prognostic group. Moreover, a significant rise in the absolute counts of DNT cells in each prognostic group and in the low‐risk prognostic group of NKT‐like cells was found. A significant correlation of the absolute values of NKT‐like cells in the intermediate‐risk prognostic group versus B cells was observed. Furthermore, we analyzed whether the increase in T cells was related to the subpopulations of interest. Only DNT cells were positively correlated with the increase in CD3+ T lymphocytes, regardless of the stage of the disease, supporting the hypothesis that this T‐cell subset plays a key role in the immune T response in B‐CLL. Conclusion These early results supported that DNT, DPT, and NKT‐like subsets may be related to disease progression and should encourage further studies aimed at identifying the potential immune surveillance role of these minority T subpopulations.